2004
DOI: 10.1021/bi048047a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Organization in Striated Domains Induced by Transmembrane α-Helical Peptides in Dipalmitoyl Phosphatidylcholine Bilayers

Abstract: Transmembrane (TM) alpha-helical peptides with neutral flanking residues such as tryptophan form highly ordered striated domains when incorporated in gel-state 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) bilayers and inspected by atomic force microscopy (AFM) (1). In this study, we analyze the molecular organization of these striated domains using AFM, photo-cross-linking, fluorescence spectroscopy, nuclear magnetic resonance (NMR), and X-ray diffraction techniques on different functionalized TM peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(53 citation statements)
references
References 31 publications
5
48
0
Order By: Relevance
“…In principle, it is possible that these results are simply because of more favorable excimer formation by pyrene moieties in antiparallel peptides than in parallel peptides. However, this is unlikely, because we have previously shown that excimer formation also occurs in parallel peptides under certain conditions (18). Therefore, the most straightforward interpretation of our data is that there is only direct contact between antiparallel helices.…”
Section: Helix-helix Association As Analyzed By Pyrene Excimer Fluorementioning
confidence: 66%
See 1 more Smart Citation
“…In principle, it is possible that these results are simply because of more favorable excimer formation by pyrene moieties in antiparallel peptides than in parallel peptides. However, this is unlikely, because we have previously shown that excimer formation also occurs in parallel peptides under certain conditions (18). Therefore, the most straightforward interpretation of our data is that there is only direct contact between antiparallel helices.…”
Section: Helix-helix Association As Analyzed By Pyrene Excimer Fluorementioning
confidence: 66%
“…The pyrenelabeled peptides pyr N -WALP23 (Ac-C(pyrene)-GWW(LA) 8 LWWAamide) and pyr C -WALP23 (Ac-GWW(LA) 8 LWWGC(pyrene)-amide) were synthesized as described earlier (18). The fluorescent probe N-(1-pyrene)maleimide was obtained from Molecular Probes Europe BV (Leiden, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…The model depicts the striated domains as a regular array of linetype depressions with a repeat distance of 8 nm and consisting of linear peptide aggregates flanked by some lipids that are disordered and have lost their acyl chain tilt. Subsequent research using multiple techniques showed that these initial models were largely correct (Sparr et al, 2005). Gold-labeling experiments showed that the peptides were localized in the line-type depressions and in the striated domains.…”
Section: Molecular Organization Of Striated Domainsmentioning
confidence: 99%
“…The domain thus is the end result of peptide-peptide interactions in the linear peptide aggregate and lipid-peptide interactions along the peptide arrays. These insights into the organization of the line-type depressions and the striated domains, together with studies on the temperature dependence of these systems, led to a proposal of the mechanism of formation of the striated domains (Sparr et al, 2005). …”
Section: Molecular Organization Of Striated Domainsmentioning
confidence: 99%
“…Of special interest is the lateral heterogeneity induced by WALP in otherwise smooth DPPC bilayers as mixed lipid/peptide microdomains with a distinct striated appearance are spontaneously formed (Rinia et al, 2002). The striated pattern is built-up from rows of gel-state lipids with a modified packing, which alternate with single rows of the shorter WALP23 (Sparr et al, 2005). Driving forces are believed to be competing lipid packing effects and lipid-peptide interactions.…”
Section: Introductionmentioning
confidence: 99%